Assessment Of Contraceptive Knowledge and Practices Among Reproductive Age Group of Women in Urban Slums of Raipur City, Chhattisgarh, India - Bandhi, Gayatri; Bhawnani, Dhiraj; Verma, Nirmal; Soni, Gopal P (National Journal of Community Medicine, 2014)
Background: India’s population as per 2011 census was 1.21 billion. India was the first country to launch National Family Planning Program in 1952. There is development in the acceptance of family planning methods but not up to the level that is expected to stabilize the population. Therefore this study was conducted to assess the level of awareness and practices of contraception among eligible married women of urban slums of Raipur City. Methodology: A cross sectional community based study was conducted using cluster sampling in urban slums of Raipur city from November 2011 to October 2012. During the study, 711 fecund married women, age group 15-49 years were included and predesigned and pretested proforma was used as a study tool. The obtained data were analyzed using appropriate statistical test. Results: In the present study out of 711 women, 91.56 % women were aware of one or multiple methods of contraception and 53.02% used or are using contraception at the time of study. Among those 49.23% and 3.8% used permanent and temporary methods respectively. The proportion of current non-users was 32.9% in current study. The major reasons for their non-use are Anemia, weakness, lactational amenorrhea (47.01), fear of side effect (29.49%), Compulsion of non use by husband (13.67%). Conclusion: There is wide gap between awareness and practice regarding contraception. Extended efforts are required to make them understand the importance and to follow the contraception.